Transcatheter Aortic Valve Replacement Using the Portico System: 10 Things to Remember. (5th August 2016) - Tzikas, Apostolos; Amrane, Hafid; Bedogni, Francesco; Brambilla, Nedy; Kefer, Joelle; Manoharan, Ganesh; Makkar, Raj; Möllman, Helge; Rodés‐Cabau, Josep; Schäfer, Ulrich; Settergren, Magnus; Spargias, Konstantinos; et al.
Abstract : The Portico system (St. Jude Medical, Minneapolis, MN, USA) consists of a self‐expanding valve prosthesis and a delivery system designed for transcatheter aortic valve replacement (TAVR). We describe this system, its 10‐steps implantation procedure, and provide tips and tricks based on our personal experience with this system.